1999
DOI: 10.1023/a:1008919408855
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The findings relating to magnetic field exposures directly measured by personal monitoring support an association with the risk of childhood leukemia. As exposure assessment is refined, the possible role of magnetic fields in the etiology of childhood leukemia becomes more evident.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Accumulation of these free radicals can cause oxidative stress [ 32 , 53 , 76 ], and the oxidative stress causes a change in the enzymatic activity, gene expression, and the release of calcium from intracellular stores. Moreover, this stress can affect the membrane structure and cell growth, and induce cell death (apoptosis) [ 71 , 77 , 78 ]. By treating soybean seeds by SMFs, Shine and Guruprasad [ 79 ] observed an enhancement in the production of the ROS mediated by cell wall peroxidase, while the production of ascorbic acid content, and SOD and APX activities were decreased in the hypocotyl part of the germinating seeds.…”
Section: The Effects Of Mf Application On Plant Developmentmentioning
confidence: 99%
“…Accumulation of these free radicals can cause oxidative stress [ 32 , 53 , 76 ], and the oxidative stress causes a change in the enzymatic activity, gene expression, and the release of calcium from intracellular stores. Moreover, this stress can affect the membrane structure and cell growth, and induce cell death (apoptosis) [ 71 , 77 , 78 ]. By treating soybean seeds by SMFs, Shine and Guruprasad [ 79 ] observed an enhancement in the production of the ROS mediated by cell wall peroxidase, while the production of ascorbic acid content, and SOD and APX activities were decreased in the hypocotyl part of the germinating seeds.…”
Section: The Effects Of Mf Application On Plant Developmentmentioning
confidence: 99%
“…Such surrogates include the configuration of power line wiring, from both distribution and high voltage overhead transmission lines [57]; present day measurement of magnetic fields within residences [8, 9] or present day personal measurements [10, 11]; distance to transmission lines [1214]; or historical calculated fields [1520]. Each approach has distinct advantages and limitations.…”
Section: Introductionmentioning
confidence: 99%
“…This early research brought the issue of magnetic field-related health risks to the attention of scientists and the public. Two studies by Green et al [13] and Schuz et al [14] have reported an association between Extremely Low Frequency -Electric and Magnetic Field (ELF-EMF) and Leukemia. The strongest evidence that ELF-EMF exposures pose health effects comes from associations observed in human populations with two forms of cancer: childhood leukemia and chronic lymphocytic leukemia in occupationally exposed adults.…”
Section: Elf-emf Associated Health Hazardmentioning
confidence: 99%
“…The epidemiological studies and health reports by California Department of Health, California EMF Program, [20], the Bioinitiative report by David Carpenter and Cindy Sage [19], Dockerty et al [30], Feychting and Ahlbom [21], Lee et al [27], Green et al [13], Loomis et al [22], Linet et al [31], McBride et al [32], Neutra et al [23], Savitz et al [33], Schuz et al [26], US National Institute of Environmental Health Sciences [34], and Wertheimer and Leeper [12], demonstrate a fairly consistent pattern of small increased risk with increasing exposure. However, no indication of increased leukemia in experimental animals has been observed.…”
Section: Elf-emf Associated Health Hazardmentioning
confidence: 99%